“The Isle is Full of Noises”: C Force and Musical Life in The Bahamas - LeGrand, Cathleen (International Journal of Bahamian Studies, 2015)
C Force, the faculty ensemble from The College of The Bahamas, is a powerful tool for music education. The ensemble blends performance, recording, arrangement, instruction, and musical discovery in ways that create new opportunities for teaching and learning about music.